POTRET KEMAMPUAN LITERASI DAN NUMERASI SISWA SEKOLAH DASAR DI WILAYAH 3T: STUDI DI WAMENA, PAPUA PEGUNUNGAN - Sari, Rita; Ambarita, Yogi Marulitua; Romrome, Abel Yohanis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low literacy and numeracy skills of elementary school students remain a challenge in education, particularly in remote areas such as Wamena, Highland Papua, influenced by limited learning facilities, teacher quality, and language barriers. Therefore, this study aimed to measure students’ literacy and numeracy levels in Wamena based on three main questions: (1) what is the level of students’ literacy in elementary schools in Wamena, (2) what is the level of students’ numeracy in elementary schools in Wamena, and (3) how do literacy and numeracy achievements differ among schools. The approach employed in this study was a quantitative approach using a descriptive research design. The sample consisted of 136 fourth- and fifth-grade students from four elementary schools: SD Napua, SD Negeri Hom-Hom, SD Yiwika, and SD Waga-waga. Data were collected through reading literacy and numeracy tests based on the Minimum Competency Assessment (AKM) framework and analyzed using descriptive statistics. The results revealed that students’ literacy skills were in the moderate category with an average score of 59.4, while numeracy skills were in the low category with an average score of 52.7. Most students remain in the low category, especially in numeracy, with difficulties in comprehension, reasoning, and contextual problem solving. Differences among schools were also observed, influenced by teaching quality and learning resources. The study emphasized the need to strengthen teacher competencies, literacy and numeracy culture, and contextual learning based on local culture.